Photosynthetic characteristics of Paris polyphylla var. chinensis in response to different light intensities and soil water contents - Zhang, Yaling; Xu, Rong; Wang, Zhaozhao; Zhang, Juan; Tang, Xinghao; Chen, Yu; Yan, Xiao-Li; Qu, Lu-Ping (Frontiers in Plant Science, 2025)
IntroductionParis polyphylla var. chinensis (Franch.) Hara (P. polyphylla) is a perennial medicinal plant with a reputation for therapeutic properties. It is imperative to study the photochemical processes of P. polyphylla in order to determine the optimal levels of shading and moisture management for its cultivation in artificial environments.MethodsIn this study, six shading levels (no shading, 30%, 50%, 70%, 80% and 90% shading) and three soil water contents (20%, 40% and 60% of the soil water saturation capacity) were established to determine the appropriate shade intensity and soil moisture content for the growth of P. polyphylla.ResultsThe results showed that only the low shade groups (no shade and 30% shade) showed irreversible damage to the daily photosynthetic dynamics of the plant over the course of a day. It is important to note that excessive light can damage not only the quantum yield for electron transport (φDo) and PSII light quantum yield (Fv/Fm), but also various physiological mechanisms that can lead to overall plant damage and a decline in organic matter. A comparison of Fv/Fm during the midday period showed that the optimum shade intensity is between 50% and 70%. Low shading can significantly increase light use efficiency (LUE), but also reduces net photosynthetic rate (Pn) and transpiration (Tr), indicating the negative effect on P. polyphylla growth. Considering the balance between growth rate and damage incidence, 50% shade should be the optimal treatment for P. polyphylla, followed by 30% and 70% shade. It was also observed that treatment with low soil water content (20%) significantly reduced Pn and LUE, while increasing stomatal conductance (gs) and water use efficiency (WUE). This is associated with a decrease in the light response curve, indicating that low soil moisture inhibits the growth of P. polyphylla and increases the likelihood of irreversible light damage, so the optimum soil moisture content for P. polyphylla should be above 20%.DiscussionConsidering the economic benefits and the growth and health of P. polyphylla in artificial cultivation, it is recommended that shade be controlled at around 50% while maintaining soil moisture between 40% and 60% of water content.